A case of ventricular noncompaction associated with heterotaxy and atrioventricular block diagnosed at 15 weeks of gestation using superb microvascular imaging. Issue 7 (1st May 2022) - Muto, Megumi; Horinouchi, Takashi; Maeno, Yasuki; Yoshizato, Toshiyuki; Mihara, Yutaro; Kusano, Hironori; Shimomura, Takuya; Sakamoto, Yoshitaka; Ushijima, Kimio
Abstract: We present a case of fetal atrioventricular block, heterotaxy, and ventricular noncompaction observed longitudinally from the first to early second trimesters using B‐mode and Doppler imaging, including superb microvascular imaging. At 12 weeks of gestation, the atrial and ventricular rates were 133 and 67 beats/min, respectively, and dextrocardia was noted. At 15 weeks of gestation, detailed sonography revealed ventricular septal defect, interruption of the inferior vena cava, dilated azygos vein, and double‐outlet right ventricle. In addition, superb microvascular imaging revealed irregular contours in the anatomical left ventricular wall, indicating prominent trabeculations of the ventricle, which were characteristic findings of ventricular noncompaction. At 21 weeks of gestation, intrauterine fetal death occurred, and the autopsy revealed complex congenital heart disease, including ventricular noncompaction.